Numerical modelling of nanocomposite conductive plate for battery thermal management using a novel multi-domain approach. (5th January 2021) - Jabbari, M.; Wang, R.; Liang, Z.; Esfahani, M.N.; Hosseinzadeh, E.
Highlights: Suggesting lightweight graphene-enhanced nanocomposites for conductive (fin) plates. Introducing new multi-domain approach for modelling battery thermal management. Noticeable cell temperature reduction is achieved using nanocomposites fin plates. Abstract: Conventional cooling approaches of lithium-ion batteries (LIBs) with targeted cell surface combined with conductive (fin) plates remains one of common ways of reducing overall cell temperature. This, however, leads to weight increase in battery cooling system as well as imposed temperature gradient on the cell surface – especially in large format batteries (with larger surface area) and at aggressive duty cycles. Using lightweight graphene-enhanced nanocomposite (GNC) plates will overcome the aforementioned hurdles by reducing the weight of cooling plates. Moreover, high conductivity of graphene will increase the cooling capacity of the conductive plates. In this paper a novel multi-domain approach (MDA) is proposed as a fast and robust method to investigate the use of GNC to reduce the overall temperature of a LIB pouch cell. A two-dimensional numerical model is firstly developed to capture the temperature distribution in a LIB pouch cell, and validated against existent results from literature. The model is then coupled with a GNC plate for cooling using MDA. The results show that using GNC plates reduces the cell average temperature about 8–27% and 3–16% at 3 C and 5 C discharge rate, respectively, while reducing the weight about 38–72%.